Clinical Evaluation of a Portable System for Capturing Nystagmus (PSCN) as an Alternative to Videonystagmography - Sefein, Maher Fouad; Teo, Kenneth Teze Kin; Lim, Christopher; Firdaus, Mohamed; Patawe, Patawari; Ong, Cheng Ai; Prepageran, Narayanan (Gazi University, 2019)
Objective: To develop a portable and affordable system for diagnosing pathological horizontal nystagmus (oscillatory rapid eye movement) in remote clinics. It is aimed to be a temporary alternative to the golden standard tool which is the Video Nystagmography which is expensive and office-based equipment. Method: The team created a system composed of a hardware gadget and software application. The modified goggle with a built-in camera and microcontroller is used to record and analyze the induced nystagmus. The analyzed data is then transmitted via Bluetooth to the user portable device which displays the results. Programming PSCN, it was tested in the outpatient clinic. During the clinical evaluation of the gadget, the nystagmus was induced and recorded by the Video Nystagmography. Immediately, we repeated the experiment using the created system. Eventually, the two results were compared to set up the thresholds in the new system. After calibration, the amended algorithm of PSCN tested another ten recorded nystagmus videos to evaluate its accuracy. Results: The portable system showed high clinical reliability during the testing in comparison to golden standard Videonystagmography. In the second stage, it showed an accuracy ratio up to 80 % during testing the ten recorded videos. It also managed to differntiate the real nystagmus from the artifacts. Conclusion: This trial proofed the concept of portable system as an assistive diagnostic tool for pathological nystagmus. However, a more clinical trial is required to establish it as a portable alternative for the golden standard. © Copyright 2019 by Gazi University Medical Faculty.